Students’ Perspectives on Mobile Phone Use in Developing Their Learning Habits - Gurung, Khum Bahadur (An ENDEAVOUR: Journal of Academia and Research, 2026)
This study examines the perspectives of 8th grade students in Waling Municipality concerning the impact of mobile phone use on their learning traits. Despite local restriction, the advantages and risks of mobile technology on academic pursuit of students remain as key concerns for educators and guardians. The study adopted a quantitative research design, collected data from 214 students across 10 different private schools of Waling Municipality using a structured questionnaire and analyzed data via IBM SPSS Statistics (version 20.0). The results show that 86% of students make use of mobile phones for academic activities and 86.4% report the use of AI tools for schoolwork. Nonetheless, as descriptive analysis depicted, approximately 40% of students reported to have been distracted due to gaming and social media. The findings further underscore gap in parental monitoring that 66% of students reported facing a strict rule-bound mediation which lacked explanatory guidance. However, students used frequently mobile technology for routine homework with the mean (M=2.307), whereas use for creative and explorative purposes remained low. The study concludes instead of restrictive pattern, guidance-based monitoring is indispensable to enhance students’ self-regulated learning. The findings suggest that educational policies in semi-urban contexts like Waling Municipality should emphasize on well-planned digital integration and mentoring to ensure impactful use of mobile technology for academic excellence of students.